Fabrication of Mesoporous Silica/Alumina Hybrid Membrane Film Nanocomposites using Template Sol-Gel Synthesis of Amphiphilic Triphenylene - H O Lintang; M A Jalani; L Yuliati; M M Salleh (IOP Publishing, 2024)
Indexed by SCOPUS